Catalytic Antioxidants in the Kidney - Yu Ah Hong; Cheol Whee Park (Antioxidants, 2021)
Reactive oxygen species and reactive nitrogen species are highly implicated in kidney injuries that include acute kidney injury, chronic kidney disease, hypertensive nephropathy, and diabetic nephropathy. Therefore, antioxidant agents are promising therapeutic strategies for kidney diseases. Catalytic antioxidants are defined as small molecular mimics of antioxidant enzymes, such as superoxide dismutase, catalase, and glutathione peroxidase, and some of them function as potent detoxifiers of lipid peroxides and peroxynitrite. Several catalytic antioxidants have been demonstrated to be effective in a variety of in vitro and in vivo disease models that are associated with oxidative stress, including kidney diseases. This review summarizes the evidence for the role of antioxidant enzymes in kidney diseases, the classifications of catalytic antioxidants, and their current applications to kidney diseases.